Design of a Web Application to Increase the Sales of the Company Neverland in Lima, Peru - García Paraizaman, Anaclaudia (2023)
Nowadays, the internet has become the most popular tool used to communicate and exchange information, but it is not very feasible due to the lack of knowledge of its proper use related to digital skills, hindering its benefits in the business part, as well as limited in the aspect of advertising and not very dynamic in the part of interaction with the customer. Therefore, the main objective that has been proposed is to design a web application to increase the sales of the company Neverland, Lima-2022. In the construction of the web application, the Visual Studio tool was used, plus the incorporation of a database in Microsoft SQL Server, where all the information within the web application is stored. The methodology applied is Scrum and Smart, which helped us to structure the project; where based on the user stories. The final product was obtained, the design of the web application of the Neverland Company. In order to measure the results, we incorporated a questionnaire for the company's clients to test its functionality. As a result, a high satisfaction rate of 96% was obtained, validating the web application for use in the Neverland Company. The conclusions show that implementing the web application generates greater productivity and control in sales orders in the company Neverland, Lima-2022. In addition to improving interaction with clients, it guarantees an increase in the number of clients and optimization of resources. In the future, the use of its own domain is contemplated.